2020
DOI: 10.1002/2211-5463.12992
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 knockdown ameliorates liver insulin resistance by activating IRS‐2 phosphorylation through the AKT and ERK1/2 signaling pathways

Abstract: Here, we report that SHP2 knockdown enhances glucose consumption, ameliorates insulin resistance, activates IRS‐2 and AKT, and inhibits ERK1/2 phosphorylation in liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
(41 reference statements)
0
10
0
Order By: Relevance
“… 85 Two other studies also reported that SHP2 promoted insulin resistance by regulating the insulin receptor substrate through Akt/ERK signaling pathways. 86 , 87 Liu et al also demonstrated that conditional knockout of SHP2 in macrophages or pharmacological inhibition of SHP2 ameliorated high-fat diet induced hepatic steatosis and insulin resistance by elevating IL-18 levels. 88 Therefore, SHP2 may be a strategic target for T2DM treatments.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 98%
“… 85 Two other studies also reported that SHP2 promoted insulin resistance by regulating the insulin receptor substrate through Akt/ERK signaling pathways. 86 , 87 Liu et al also demonstrated that conditional knockout of SHP2 in macrophages or pharmacological inhibition of SHP2 ameliorated high-fat diet induced hepatic steatosis and insulin resistance by elevating IL-18 levels. 88 Therefore, SHP2 may be a strategic target for T2DM treatments.…”
Section: The Signaling Pathways Regulated By the Protein Phosphatases...mentioning
confidence: 98%
“…The effects seen upon SHP2 (PTPN11) gene disruption (conditional knockout models) are variable and highly tissue dependent, probably due to the pleiotropic role of SHP2 in various growth factor pathways. Nevertheless, multiple experiments support that inhibition of SHP2 activity in the liver (but not in the skeletal muscle or pancreas) can ameliorate insulin resistance in mouse models 5 , 38 40 . In accordance with animal experiments, individuals with hereditary SHP2 gain-of-function mutations (Noonan syndrome) display insulin resistance more frequently than the generic population, despite their overall leaner phenotype 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Glycolipid metabolism-related genes were IRS2, G6PC, MYC, SREBF1, GCK, FASN, HMGCR, CYP7A1, PLIN1, ELOVL6, and SCD2. IRS2, an important gene in the insulin signaling pathway, is closely related to the process of insulin resistance . G6PC is a rate-limiting enzyme in the gluconeogenesis and glycogenolysis, and the changes of its activity and expression directly affect the output of endogenous sugars .…”
Section: Discussionmentioning
confidence: 99%